2002
DOI: 10.1634/theoncologist.7-2-136
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nonmalignant Systemic Disease on Tolerance to Radiation Therapy

Abstract: Purpose. Some patients with nonmalignant systemic diseases, like collagen vascular disease (CVD), hypertension, diabetes mellitus, and inflammatory bowel disease (IBD), tolerate radiation therapy poorly. Although the mechanisms of each of these disease processes are different, they share a common microvessel pathology that is potentially exacerbated by radiotherapy. This article reviews and evaluates available data examining the effects of these benign disease processes on radiation tolerance.Methods. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 37 publications
3
48
1
1
Order By: Relevance
“…Diabetes mellitus was the only variable in this current study identified as a statistically significant predictor of acute skin toxicity on univariable (p<0.001) and multivariable (p=0.003, OR 95%CI = 5.00-30.82) analyses, similar to what has been observed in some other trials [38,39]. In contrast, other groups have reported no significant correlation between diabetes mellitus and acute skin toxicity [29].…”
Section: Discussionsupporting
confidence: 87%
“…Diabetes mellitus was the only variable in this current study identified as a statistically significant predictor of acute skin toxicity on univariable (p<0.001) and multivariable (p=0.003, OR 95%CI = 5.00-30.82) analyses, similar to what has been observed in some other trials [38,39]. In contrast, other groups have reported no significant correlation between diabetes mellitus and acute skin toxicity [29].…”
Section: Discussionsupporting
confidence: 87%
“…Morris and Powell 11 reported that severe late effects were associated with CVD other than RA, a finding that was also supported by a meta-analysis by Chon and Loeffler. 12 Other studies suggest that a diagnosis of scleroderma 13,14 or lupus 15 may increase the risk of RTassociated toxicity. However, 2 separate matched control studies failed to observe any increased risk of acute or late complications in patients with CVD versus patients without CVD.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, 2 separate matched control studies failed to observe any increased risk of acute or late complications in patients with CVD versus patients without CVD. 9,10 Other publications suggested that patients with nonrheumatoid arthritis CVD, 11,12 or patients with specific subtypes of CVD, may be at increased toxicity risk. [13][14][15] Further complicating the issue is the finding that some commonly prescribed medications, many of which are used in patients with CVD, may alter the radiation toxicity profile.…”
mentioning
confidence: 99%
“…Even within a group of identically treated patients, large variability exists in both the incidence and severity of radiation toxicity, partly the result of the random nature of radiation-induced cell mortality and the variability in intrinsic cellular radiosensitivity among individuals. It is also due to certain cofactors, such as age; hemoglobin level; smoking habits; and the presence of diabetes mellitus, hypertension, or inflammatory bowel disease (25,26). Therefore, particularly in women with both a diagnosis of SLE and breast cancer, RT with curative intent could be prescribed more often to those who wish to avoid a complete mastectomy.…”
mentioning
confidence: 99%
“…Prospective, randomized controlled trials have shown that in patients with operable breast cancer, the outcome after BCS followed by radiation was equivalent to that of mastectomy with respect to local and distant recurrence, as well as overall survival (28). Currently, the recommended radiotherapy technique includes treatment of the entire breast with tangential opposed fields using Cobalt 60 beam or X-rays (26). Acute skin reactions during RT of the breast occur in ϳ50% of the cases, and may include brisk erythema to confluent moist desquamation (29).…”
mentioning
confidence: 99%